2021
DOI: 10.3390/jmse9040400
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Validation of the Two-Way Fluid-Structure Interaction Method for Non-Linear Structural Analysis under Fire Conditions

Abstract: Fire accidents on ships and offshore structures lead to complex non-linear material and geometric behavior, which can cause structural collapse. This not only results in significant casualties, but also environmental catastrophes such as oil spills. Thus, for the fire safety design of structures, precise prediction of the structural response to fire using numerical and/or experimental methods is essential. This study aimed to validate the two-way fluid-structure interaction (FSI) method for predicting the non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…The interaction between fire simulation and ship structural analysis is considered assuming that all other parameters remain constant. Woo [28] adopted numerical and experimental validation of the two-way fluid-solid coupling (FSI) method for predicting the nonlinear structural response of H-beams to propane burner fires, showed that the two-way FSI method can accurately predict the nonlinear structural response of H-beams to propane burner fires, and suggested appropriate time increments for two-way FSI analyses. Wang [29] further examined the smoke plume entrainment and filling behavior in closed ship cabin fires, proposed a corresponding theoretical model, applied the particle swarm optimization coupled smoke filling model for inverse analysis, and established a sealed cabin fire model suitable for engineering safety design from a practical point of view.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The interaction between fire simulation and ship structural analysis is considered assuming that all other parameters remain constant. Woo [28] adopted numerical and experimental validation of the two-way fluid-solid coupling (FSI) method for predicting the nonlinear structural response of H-beams to propane burner fires, showed that the two-way FSI method can accurately predict the nonlinear structural response of H-beams to propane burner fires, and suggested appropriate time increments for two-way FSI analyses. Wang [29] further examined the smoke plume entrainment and filling behavior in closed ship cabin fires, proposed a corresponding theoretical model, applied the particle swarm optimization coupled smoke filling model for inverse analysis, and established a sealed cabin fire model suitable for engineering safety design from a practical point of view.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Methods for determining fire loads on ships and offshore structures have been actively investigated [3][4][5][6][7], along with the responses of structures exposed to fire loads [8][9][10] and efficient fire suppression system design principles [11]. Additionally, although large spaces have been studied [12][13][14], previous studies did not consider pool spread characteristics under ship motion.…”
Section: Introductionmentioning
confidence: 99%
“…HSE (2007) reported that fire and explosion were considered the main hazards in more than 60 offshore accidents that occurred in the last 40 years [4], such as the Sanchi oil tanker accident on 6 January 2018 in the East China Sea and the U.S.S. Bonhomme Richard accident on 12 July 2020 in San Diego shown in Figure 1 [5,6].…”
Section: Introductionmentioning
confidence: 99%